Ensuring Legal Protection for Consumers of Halal-Certified Minang Cuisine in Padang City - Mardhika Adif, Riandy; Jefriyanto, Jefriyanto; Setia Putra, Hari (Takaza Innovatix Labs Ltd., 2024)
This study aims to understand legal protection for consumers in Padang City to establish a model for consumer protection practices in Indonesia. The research employs a normative descriptive qualitative method, focusing on business operators and consumers of traditional Minang products, with data collected through interviews. The study reveals that legal protection for consumers concerning halal labels on Minang food is stipulated in Law No. 08 of 1999. Several reasons contribute to producers not including halal labels: high processing costs, lack of awareness about the importance of halal certification, and consumers' inherent trust in authentic Minang producers, even if the shop lacks halal certification. The Indonesian Ulema Council (MUI) asserts that Muslim-owned businesses should pursue halal certification regardless of the owner's religion.